2020
DOI: 10.21203/rs.3.rs-16570/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overexpression of TGFβ1 in murine mesenchymal stem cells improves lung inflammation by impacting the Th17/Treg balance in LPS-induced ARDS mice

Abstract: Abstract Background: T helper 17 cells (Th17) /regulatory T cells (Treg), as subtypes of CD4 + T cells, play an important role in the inflammatory response of acute respiratory distress syndrome (ARDS). However, there is still a lack of effective methods to regulate the differentiation balance of Th17/Treg. It was proven that mesenchymal stem cells (MSCs) could regulate the differentiation of CD4 + T cells, but the mechanism is still unclear. TGFβ1, a paracrine cytokine… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…By establishing an in vitro coculture system with LPShypoxia stimulation on CD4 + T cells, we found that MSC coculture restored skewed Treg/Th17 and significantly augmented the anti-inflammatory cytokine secretion. We have proved that MSCs overexpressing TGF-β1 could regulate lung inflammation and attenuate lung injuries by modulating the imbalance of Th17/Treg in the lungs of ARDS mice [12]. Establishing an in vitro cell coculture model with LPS and hypoxia challenge would promote our knowledge in the interaction between Treg and Th17 cell skewing and MSCs in a specific condition.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…By establishing an in vitro coculture system with LPShypoxia stimulation on CD4 + T cells, we found that MSC coculture restored skewed Treg/Th17 and significantly augmented the anti-inflammatory cytokine secretion. We have proved that MSCs overexpressing TGF-β1 could regulate lung inflammation and attenuate lung injuries by modulating the imbalance of Th17/Treg in the lungs of ARDS mice [12]. Establishing an in vitro cell coculture model with LPS and hypoxia challenge would promote our knowledge in the interaction between Treg and Th17 cell skewing and MSCs in a specific condition.…”
Section: Discussionmentioning
confidence: 91%
“…Coculture System. Mouse bone marrow MSCs were purchased from Cyagen Biosciences Inc. (Guangzhou, China), which has been identified by detecting cell surface markers with ≥90% positivity for expression of cell surface antigens CD29, CD44, and CD105 and ≤5% positivity for expression of cell surface antigens CD45 and CD34 [12], and cells were 2…”
Section: Bone Marrow-derived Msc-treated Cd4 + T Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…11,13 Therefore, the balance of the Th17/Treg is critical in the inflammatory response to ameliorate lung inflammation by a uniform balance of Th17/Treg. 14,15 A deficiency of vitamin D can impede the downregulation of Th17 cells and the upregulation of Treg cells, thus unbalancing the proportion of Th17/Treg. 16 Currently, no investigation has determined whether vitamin D can regulate the airway inflammation of asthmatic mice by regulating the balance of Th17/Treg.…”
mentioning
confidence: 99%